Perempuan Dalam Perjuangan Bersama Rasulullah: Studi Kasus Tentang Umm 'Athiyyah: Women in the Struggle Alongside the Prophet: A Case Study of Umm ‘Athiyyah - Aminullah Elhady (Fenomena, 2002)
Women’s direct involvement in battle remains a rare and debated phenomenon across both classical and modern societies. Within Islamic tradition, the prophetic era offers historical precedents that warrant critical examination through the science of hadith. This study evaluates the authenticity of narrations about Umm ‘Athiyyah, a female companion who reportedly participated in seven military expeditions alongside Prophet Muhammad. Using takhrij al-hadith and sanad criticism methods across four primary sources—Sahih Muslim, Sunan Ibn Majah, Musnad Ahmad, and Sunan al-Darimi—this research traces all chains of transmission and assesses each narrator’s credibility. The findings confirm that all sanad chains are connected (muttasil), all narrators meet the criteria of tsiqah (trustworthy), and the transmission occurs through mu’asharah (contemporaneity), establishing the hadith as sahih (authentic). The study concludes that Islam permits women’s participation in supporting combat roles, including medical care and logistics, while distinguishing such roles from direct frontline fighting. Recommendations include revisiting classical jurisprudence on women’s wartime rights and further contextualizing prophetic traditions for contemporary defense policies. Keterlibatan langsung perempuan dalam peperangan merupakan fenomena yang langka dan diperdebatkan, baik dalam masyarakat klasik maupun modern. Dalam tradisi Islam, era kenabian menyediakan preseden historis yang memerlukan kajian kritis melalui ilmu hadits. Penelitian ini bertujuan mengevaluasi otentisitas periwayatan tentang Umm ‘Athiyyah, sahabat perempuan yang dilaporkan terlibat dalam tujuh peperangan bersama Rasulullah. Menggunakan metode takhrij al-hadits dan kritik sanad pada empat sumber primer—Shahih Muslim, Sunan Ibn Majah, Musnad Ahmad, dan Sunan al-Darimi—penelitian ini menelusuri seluruh rantai periwayatan dan menilai kredibilitas setiap perawi. Hasil penelitian membuktikan bahwa seluruh sanad bersambung (muttasil), semua perawi memenuhi kriteria tsiqah (terpercaya), dan terjadi kesegenerasian (mu’asharah), sehingga hadits berstatus sahih. Kesimpulannya, Islam mengizinkan perempuan berperan serta dalam peperangan pada posisi pendukung, seperti perawatan medis dan logistik, namun membedakannya dari pertempuran garis depan. Rekomendasi penelitian mencakup peninjauan kembali fikih klasik tentang hak-hak perempuan di medan perang serta kontekstualisasi lebih lanjut tradisi kenabian untuk kebijakan pertahanan kontemporer.